Withstanding Vulnerability throughout Adult Life Dynamics of Stressors, Resources, and Reserves - Spini, Dario; Widmer, Eric (Springer Nature, 2023)
This open access interdisciplinary book integrates the major findings and theoretical advances of a 12-year research program run by the Swiss National Centre of Competence in Research LIVES research program hosted by the universities of Lausanne and Geneva, within a single comprehensive and coherent publication on vulnerability across adulthood. The book is based on the idea that vulnerability is an essential component of the life course that can inform how we use our resources, reserves and cope with stressors across the life course. It provides a unique interdisciplinary research framework based on the idea that vulnerability is a complex and dynamic process that can only be approached through a multidimensional, multilevel, and multidirectional perspective. This is an invaluable new resource for students and researchers in life course studies, and those from other disciplines willing to include life course factors in their research on vulnerability issues.